Examining the Inter-Linkages of COVID-19, Agricultural Households and Nepal’s Political Economy - Pokhrel, Pankaj; G.C., Shreezal; Sharma, Sudhindra (Economic Journal of Development Issues, 2023)
This study investigates the economic repercussions of the COVID-19 pandemic on Nepal’s political economy and household economies, focusing on the agricultural sector and remittance dynamics. The primary objective is twofold: first, to analyze the pandemic’s impact on Nepal’s broader economic landscape using secondary literature, and second, to examine the consequences of outmigration on household economies through primary panel data from 2017 and 2020 surveys. The methodology involves employing a mix of secondary literature analysis and primary panel data from five districts, using OLS and random effects models to evaluate the effects on agricultural yield. The results indicate that the agricultural output of migrant households did not significantly increase post-pandemic, while non-migrant households experienced a notable rise in average agricultural yield. This suggests the resilience of traditional agricultural and food systems during shocks. The study underscores the importance of policies encouraging migrant households to leverage remittances for agricultural productivity and emphasizes the need for long-term strategies to enhance overall economic resilience in the face of global crises.